The Intersection of Language and Disability Progress of English Learners With Disabilities on NAEP Reading - Shenghai Dai; Yuliya Ardasheva
Despite evidence of unequal learning opportunities, there is limited understanding of how English learners (ELs) with disabilities are faring academically nationwide in comparison with their EL and student with disability counterparts. In response, we conducted secondary data analyses of the 2009 to 2019 National Assessment of Educational Progress (NAEP) reading assessments. Compared to their peers, ELs with disabilities performed lower in both Grades 4 and 8. There is a visible improvement in this important student population$1 (Bs performance on the NAEP 2015 reading assessment$1 (Ba year in which disaggregated reporting for ELs with disabilities performance became mandatory. These findings have implications for improved instructional, assessment, and program supports to serve ELs with disabilities.s